"Our quality is a little bit different": How family childcare providers who participate in a Quality Rating and Improvement System and receive childcare subsidy define quality. (March 2021) - Hooper, Alison; Hallam, Rena; Skrobot, Christine
This research uses focus group methodology to examine how a specific subset of family childcare providers—those participating in a voluntary quality rating and improvement system and serving a high percentage of children receiving childcare subsidy—define quality. The study builds on the limited existing research about family childcare quality, especially research focused on understanding quality from the perspective of the childcare provider. A total of 28 family childcare providers participated in three focus groups where they were asked to define quality and to describe high- and low-quality programs. Qualitative analysis revealed four themes: relationships, supporting children's learning, the physical and temporal environment, and personal professionalism. These results can inform how quality improvement initiatives and professional development systems support and engage family childcare providers.